수산화 칼슘 보충제의 피부세포 증식 향상을 통한 상처 치유 효과 - 이지연(Ji Yeon Lee); 김진우(Jin-Woo Kim); 장판식(Phan-Shick Chang); 김진철(Jin-Chul Kim) (한국식품과학회지, 2024)
수산화 칼슘 보충제의 상처 치유 활성에 대한 가능성을 인체유래 각질 세포 및 인간 섬유아세포를 이용하여 검증하였다. 본실험 조건에서 수산화 칼슘 보충제는 직접적인 처리를 통해서는HaCaT의 이동능을 촉진시키지 못하였다. 하지만, 수산화 칼슘 보충제를 처리한 HDF 조건 배지를 HaCaT에 처리하였을 때, HaCaT 세포의 이동능 및 증식을 유의적으로 촉진하였다. Western blot을통해 HDF의 신호전달에 의해 세포의 증식에 관여하는 단백질들의 발현을 측정한 결과, HDF-조건 배지 처리군과 비교하였을 때수산화 칼슘 처리 HDF-조건 배지 처리군에서 GS3K-β/β-catenin 기전의 활성이 증가하였고, 이를 통해 수산화 칼슘 보충제가 HDF 세포의 HaCaT 세포 성장 물질을 분비를 촉진시키는 것으로 예상할 수 있으며, 본 연구 결과는 피부 상처 회복 효과에 대한 수산화 칼슘 보충제의 이용가능성을 시사한다. This study aimed to evaluate the impact of calcium hydroxide supplement (CHS) on wound healing using human keratinocytes and elucidate its underlying cellular mechanisms. Although CHS did not directly promote human keratinocyte (HaCaT) migration, it exhibited a wound healing effect on HaCaT cells in CHS-treated human dermal fibroblast (HDF)-conditioned media (CM). Compared with cells treated with HDF-CM alone, cell migration was significantly increased (37.6%) upon treatment with 1.6 μg/mL of CHS-treated HDF-CM. Treatment with CHS-treated HDF-CM significantly activated GS3k-β/β-catenin signaling pathways, which are key mediators of cell proliferation. These results indicate that CHS possesses wound healing potential and provide a molecular basis for the development of functional natural products for wound healing. KCI Citation Count: 0